How can I help you? Design principles for task-oriented speech dialog systems in customer service - Thuy Duong Oesterreich; Eduard Anton; Julian Schuir; Alexander Brehm; Frank Teuteberg (Information Systems and e-Business Management, 2022)
Organizations are increasingly delegating customer inquiries to speech dialog systems (SDSs) to save personnel resources. However, customers often report frustration when interacting with SDSs due to poorly designed solutions. Despite these issues, design knowledge for SDSs in customer service remains elusive. To address this research gap, we employ the design science approach and devise a design theory for SDSs in customer service. The design theory, including 14 requirements and five design principles, draws on the principles of dialog theory and undergoes validation in three iterations using five hypotheses. A summative evaluation comprising a two-phase experiment with 205 participants yields positive results regarding the user experience of the artifact. This study contributes to design knowledge for SDSs in customer service and supports practitioners striving to implement similar systems in their organizations.
Keywords: 650; Speech dialog system; Conversational agent; Design science research; Design principles; Customer service; Experiment